Nicholas Mangan - a world undone - Jaspers, Anneke; Davis, Anne (Museum of Contemporary Art Australia, 2024)
Over the past two decades, Australian artist Nicholas Mangan has created a compelling body of work that considers humanity's relationship to the natural world, taking everything from coral rubble to cryptocurrency as a point of departure. Mangan's art locates human history in the context of deep geological time. With a focus on Australia's place in the Pacific, his works reflect on how social, political and economic upheaval are connected to the material world, offering new perspectives on pressing global issues, such as the impact of extractive mining on natural resources and climate change. Published to coincide with the Australian artist's survey exhibition at the Museum of Contemporary Art Australia, A World Undone showcases works created by an artist pushing sculpture to new limits. This richly illustrated publication combines artwork, archival and process imagery, and includes an extended interview with the artist, as well as new essays by key thinkers in the fields of anthropology, philosophy, political economy and art history
Impressum: Published on the occasion of the exhibition "Nicholas Mangan: A World Undone", Museum of Contemporary Art Australia, 5 April - 30 June, 2024
1000 copies
Keywords: Mangan, Nicholas -- 1979-; Mangan, Nicholas / 1979- / Exhibitions; Ausstellungskatalog -- Museum of Contemporary Art -- 05.04.2024-30.06.2024 -- Sydney